A Study of the Initial System of the Yongle Nanzang 永乐南藏 Based on Phonological Correlations and Their Relationship with the Qishazang 磧砂藏 - Yongchao Jiang; Boxuan Wang; Renxuan Huang (Religions)
This study investigates the initial consonant system of the Yongle Nanzang 永乐南藏, the second officially printed edition of the Chinese Buddhist canon of the Ming dynasty, and its relationship to the Qishazang 磧砂藏. Based on a digital and quantitative analysis of 27,832 phonetic entries—including Fanqie 反切 and Zhiyin 直音—we apply correlation coefficients (with significance tests), hierarchical clustering, and data mining methods. The results show the following: (1) In the labial series, contrasts between aspirated and unaspirated sounds are weak; Bang 幫 and Pang 滂 are occasionally confused; and Fei 非 and Fu 敷 are merged. Voiced and voiceless initials are sometimes mixed, but full devoicing has not occurred. (2) In the coronal series, Duan Zu 端組 shows high internal interchange and Zhi Zu 知組 tends to mix with Zhang Zu 章組 and Zhuang Zu 莊組. (3) In the sibilant and affricate series, Jing 精 and Zhuang 莊 are merged; Chuan 船 and Shan 禪 also merge, while Cong 從 and Xie 邪 only occasionally alternate. (4) In the velar and laryngeal series, fully voiced Qun 羣 is close to voiceless initials, while Yun 云 and Yi 以 are closely related. Nasal and lateral initials maintain independence. The findings suggest that Yongle Nanzang 永乐南藏 is not a direct reprint of the Qishazang 磧砂藏, but rather a revised edition adapted to editorial or regional considerations. This study demonstrates the value of digital phonological methods in historical phonology and the significance of the Ming–Qing Chinese Buddhist canon.